The Existence of Li-Yorke Chaos in Certain Predator-Prey System of Difference Equations - Garić-Demirović, Mirela; Hrustić, Sabina; Moranjkić, Samra; Nurkanović, Mehmed; Nurkanović, Zehra (Sarajevo Journal of Mathematics, 2024)
This paper investigates an autonomous predator-prey system of difference equations with three equilibrium points and exhibits chaos in the sense of Li-Yorke in the positive equilibrium point. Numerical simulations are presented to illustrate our results.